2020
DOI: 10.1186/s12912-020-00447-5
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of social networking sites, their perceived benefits and their potential for improving the study habits of nursing students in five countries

Abstract: Background: The abundance of easy and accessible information and the rapid development of social networking sites (SNSs) have proven that the world is small and within reach. The great implication of this interconnectivity is attributable to the change in the learning and sharing environment, which for the most part is something that classrooms are lacking. Considering the potential implications of SNSs in nursing education reveals the benefits of SNSs in allowing students to communicate and interact with a wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
3
10
0
1
Order By: Relevance
“…Nursing students often reported using social media to learn more about academic topics, share scholarly thoughts and opinions, familiarize themselves with upcoming topics, skill improvement, and as a medium to conduct collaborative assignments and projects. [22] Students also reported that refined clinical skills obtained from use of social media platforms were positively acknowledged by clinical educators. [22] Therefore, if these educational tools are accessible to students via social media there can be many positive clinical learning outcomes.…”
Section: Accessibilitymentioning
confidence: 99%
See 4 more Smart Citations
“…Nursing students often reported using social media to learn more about academic topics, share scholarly thoughts and opinions, familiarize themselves with upcoming topics, skill improvement, and as a medium to conduct collaborative assignments and projects. [22] Students also reported that refined clinical skills obtained from use of social media platforms were positively acknowledged by clinical educators. [22] Therefore, if these educational tools are accessible to students via social media there can be many positive clinical learning outcomes.…”
Section: Accessibilitymentioning
confidence: 99%
“…[22] Students also reported that refined clinical skills obtained from use of social media platforms were positively acknowledged by clinical educators. [22] Therefore, if these educational tools are accessible to students via social media there can be many positive clinical learning outcomes.…”
Section: Accessibilitymentioning
confidence: 99%
See 3 more Smart Citations